Origin and Role of Kaolinization in Roll-Front Uranium Deposits and Its Response to Ore-Forming Fluids in the Yili Basin, China. (18th April 2018) - Liu, Z. Y.; Peng, S. P.; Qin, M. K.; Liu, H. X.; Geng, Y. Y.; Zhang, X.; Ding, B.; Xiu, X. Q.
Abstract : Kaolinite is a common mineral found in most Chinese sandstone-hosted uranium deposits. It occurs particularly in coal-bearing clastic rocks in northwest China, such as the uranium deposits in the Yili Basin, which is well known for hosting several large-scale roll-front uranium deposits. Previous studies have provided limited information on the origin of kaolinization and its role in the uranium mineralization. This study uses gas hydrocarbon, fluid inclusions, O and H isotope analysis, and scanning electron microscopy observations to investigate the formation of kaolinite in ore-hosting rocks from the Mengqiguer uranium deposit in the southern margin of the Yili Basin and to determine its role in the uranium mineralization. Results suggest that kaolinization is intense in the coal- and ore-bearing clastic rocks and that it is related to leaching of feldspar by acidic fluids. Vermicular kaolinite was formed by hydrocarbon-bearing fluid generated from coal and carbonaceous mudstone during a shallow-burial diagenetic stage at low homogenization temperatures ranging from 69 to 78°C and at relatively high salinities of 7.6−11.0 wt%  N a C l e q . Consequently, silicate minerals (such as feldspar) were leached and created secondary pores that hosted the subsequently formed uranium minerals. In contrast, micritic kaolinite was formed by infiltration of meteoric fluid enriched in U and O2 at low homogenization temperatures of 51−63°C and low salinities of 1.2−3.7 wt%  N a C l e q . U 6+ was sorbed by the micritic kaolinite through cation exchange, forming a U-bearing kaolinite complex; it was also reduced by pyrite and carbon detrital, thereby precipitating at the acidic oxidation front. The results of this study confirm that intense kaolinization is closely related to uranium mineralization in coal-bearing clastic rocks.